Overview of current immunotherapeutic strategies for glioma. (October 2015) - Calinescu, Anda-Alexandra; Kamran, Neha; Baker, Gregory; Mineharu, Yohei; Lowenstein, Pedro Ricardo; Castro, Maria Graciela
In the last decade, numerous studies of immunotherapy for malignant glioma (glioblastoma multiforme) have brought new knowledge and new hope for improving the prognosis of this incurable disease. Some clinical trials have reached Phase III, following positive outcomes in Phase I and II, with respect to safety and immunological end points. Results are encouraging especially when considering the promise of sustained efficacy by inducing antitumor immunological memory. Progress in understanding the mechanisms of tumor-induced immune suppression led to the development of drugs targeting immunosuppressive checkpoints, which are used in active clinical trials for glioblastoma multiforme. Insights related to the heterogeneity of the disease bring new challenges for the management of glioma and underscore a likely cause of therapeutic failure. An emerging therapeutic strategy is represented by a combinatorial, personalized approach, including the standard of care: surgery, radiation, chemotherapy with added active immunotherapy and multiagent targeting of immunosuppressive checkpoints.